Study of Struvite Crystals and Dietary at Risk for the Formation of Struvite Urolithiasis in Dogs in Small Animal Practices - Erni Sulistiawati Sulistio (Fakultas Kedokteran Hewan Universitas Gadjah Mada bekerjasama dengan PB PDHI, 2022)
Urolithiasis is defined as the formation of urolith or crystal in the urinary tract caused by supersaturation of urine. This study was conducted at PDHB drh Cucu Kartini S, dkk, Jakarta clinic. The data were taken from urinalysis test results of 23 dogs which suffered crystaluria and urolith stone examination of 11 dogs which suffered urolith stone post cystotomy. Most affected breeds were Shihtzu, Pug, Mini Pom, Corgi, Miniature Schnauzer, Golden Retriever. Crystaluria most detected in male dogs, while urolith stone most affected in female dogs. Dogs from 6 months to 12.5 years with a median of 5 years were affected. The urinalysis showed that dogs with crystaluria had alkaline urine (mean 8.3), 100% proteinuria, 86.9% hematuria, 41.4% pyuria. Diets is the most contributing factor in case of struvite urolithiasis, which is low water content; high in protein, magnesium, phosphorus, carbohydrates and calcium. Therapeutic diets that low in protein, phosphorus, magnesium and sufficient carbohydrates and diets with greater than 70% moisture can be an option for treatment and prevention of recurrent of struvite urolithiasis